Integration between the London and New York Stock Exchanges, 1825–19251. (6th February 2017) - Campbell, Gareth; Rogers, Meeghan
Abstract: In this article the integration between the London and New York Stock Exchanges is analysed during the era when they were still developing as asset markets. The domestic securities on both exchanges showed little sustained integration, even when controlling for the different characteristics of stocks, which implies that the pricing of securities in the US and UK was still being driven by local factors. These results place a limit on the view that the pre‐First World War period was the first era of globalization in terms of capital markets. However, there was considerable integration between New York and those listings on London that operated internationally. This suggests that the listing of foreign securities may be one of the primary mechanisms driving asset market integration.